The All-Knowing Narrator's Mental Sanctuary - Yeo, Nicole Yew Min (2018)
In the year 1946, German author Anna Seghers wrote her semi-autobiographical novella The Outing of the Dead Schoolgirls during her exile in Mexico (during 1941 to 1947). She had suffered from both physical and emotional traumas, having met with a car accident and having lost her mother while still in exile. This essay explores how Seghers’ use of childhood memory as a trope to work through trauma allows the protagonist a mental space that acts as a sanctuary to recover from trauma. The essay argues that Seghers attempts to reunite the protagonist with her mother but the plot disallows this anticipated trajectory. The protagonist’s failure to meet her mother demonstrates that a survivor (like Seghers) is unable to obtain closure, therefore causing them to repeatedly revisit the traumatic memory. The essay utilises the explanation of Dominick LaCapra, a trauma theorist and Holocaust historian, that the desire for a connection with the “dead intimates” causes trauma survivors to “invest” in the trauma memory by reliving and prolonging the experience as a “necessary commemoration or memorial” that the dead did not receive (23). These survivors are often provoked by their experiences of the war leaving the individual with recurring reminders of the dead and their memories of them. The desire to return to these memories and to commune with the dead complicates the process of working through the trauma that would enable victims to recover from their emotional and mental scars.